The Impact of the Development Trend and Policy Optimiza-tion of NEV on Guizhou Consumers' Usage Behavior Based on Its Natural Environment - Xiang Pi; Jacky Mong Kwan Watt (International Forum of Researchers and Lecturers, 2025)
The Impact of Development Trends and Policy Optimization of New Energy Vehicles (NEVs) on Consumer Usage Behavior in Guizhou explores the relationship between the evolving landscape of NEVs and consumer behavior in Guizhou, with a strong emphasis on environmental con-siderations. It argues that as consumers become more aware of environmental issues, their willingness to adopt NEVs increases, influenced by both government policies and social factors. The study highlights how effective policy optimization—such as financial incentives and educational initiatives—can enhance the adoption of NEVs. Additionally, it underscores the role of social influence in shaping consumer at-titudes and behaviors toward sustainable transportation. By examining these dynamics within the context of Guizhou's natural environment, the research provides valuable insights into creating a more sustainable transportation framework that aligns with both consumer preferences and ecological goals, based on a sample of 390 consumers.